ROLE OF THE BACKSTOP-TO-COVER THICKNESS RATIO ON VERGENCE PARTITIONING IN EXPERIMENTAL THRUST WEDGES - Storti F.; Marin R.S.; Faccenna C.; Sainz A.C. (My University, 2001)
The ratio between the thickness of the sedimentary sequences offscraped from the subducting plate (H c ) and the average thickness of the backstop (H b ) is expected to significantly influence vergence partitioning in thrust wedges. A series of simple sandbox experiments was performed to study the role of the H c /H b ratio in model thrust wedges. The results obtained show that thrust wedges with H c /H b values lower than 1 are essentially pro-ward verging, with minor retro-ward faulting; H c /H b values greater than 1 imply an increase of vergence partitioning. When a threshold value is exceeded, fully partitioned, doubly vergent thrust wedges develop. Comparison with natural submarine thrust wedges suggests that these experimental results may provide useful insights on the evolution of structural architecture at convergent margins.